Effect of Ultrasound/Ultra-high Pressure Combined with Sous-vide Cooking on the Quality of Spiced Beef - Zhenhua SHI; Daobang TANG; Huaigu YANG; Xueming LIU; Xuping WANG; Yaosheng LIN; Jinhao ZOU; Jingrong CHENG; Mingjun ZHU (Shipin gongye ke-ji)
To investigate the effect of ultrasound/ultra-high pressure combined with sous-vide processing on the quality of spiced beef, five processing methods, including low-temperature atmospheric pressure (LA), sous-vide (SV), ultrasonic and sous-vide (USV), ultra-high pressure and sous-vide (HSV), and high-temperature atmospheric pressure (HA) were selected to prepare spiced beef. The color, texture, moisture distribution, and microstructure of the finished product were measured, and a comprehensive quality analysis of the spiced beef was conducted using fuzzy mathematical sensory evaluation. The results indicated that the protein denaturation induced by HA could promote the transformation of immobile water to flowing water in beef tissue, resulting in the highest cooking loss (23.61%) and shear force (78.23 N). SV could effectively reduce the cooking loss rate and shear force of spiced beef, resulting in a more reddish color of the finished beef. Pretreated with ultrasonic or ultra-high pressure could further increase the gaps between beef muscle fibers, increase the proportion of bound water (48.57% and 29.39% respectively), reduce the shear force (34.30% and 48.50% respectively) and cooking loss rate (33.90% and 28.10% respectively) of spiced beef, thus improving the tenderness of products. Among them, USV treatment had the most significant effect in improving the water distribution and water-holding capacity of the spiced beef, owning a relatively high score (7.57) in fuzzy mathematical sensory evaluation. In conclusion, the USV technology showed obvious advantages in improving the physicochemical quality and sensory characteristics of spiced beef, making it suitable for upgrading traditional manner of spiced beef processing.